The use of teaching props to improve mathematics learning outcomes in number pattern material in STEM village Yogyakarta - Fika Ariana; Muhammad Prayito; Nurina Happy; Wisnuningtyas Wirani (Universitas Sarjanawiyata Tamansiswa, 2024)
Since mathematics is an abstract discipline, it is necessary to understand context when learning. This pilot study at SDN 1 Kentungan, a